Pelatihan Membuat Puding Buah Pada Kader Posyandu Di Kecamatan Ubud Kabupaten Gianyar Tahun 2018 - I Komang Agusjaya M; Ni Made Dewantari; Ni Made Yuni Gumala (Jurnal Pengabmas Masyarakat Sehat, 2019)
The aim of community service is that Posyandu cadres after training can make fruit pudding as an alternative to PMT variations in Posyandu. The targets were posyandu cadres in Sayan Village and Singakerta Village, Ubud District, Gianyar Regency, totaling 28 people. The method used was a lecture and practice carried out at the Sayan Village Office in Ubud District of Gianyar Regency on 29 September 2018. How to deliver the material using computer aids and LCD, then continued the practice of making fruit pudding. The pudding evaluation is made at the favorite level test with the hedonic test. In general, it was found that the taste of pudding was liked by the trainees and it was recommended to make the Chocolate Fruit Pudding as a PMT at the posyandu.Keywords: Fruit Pudding, Posyandu Cadre